Respuesta :

Answer:

(i) 7

(ii) y= (8-2x)/3 or g^-1 (x) = (8-2x)/3

Step-by-step explanation:

b) (i)   g(x) = (8-3x)/2

         g(-2)= (8-3(-2))/2

         g(-2) = (8+6)/2

         g(-2)= 14/2

         g(-2)=7

  (ii)   Now, for inverse, we just simply switch x and y and solve for y(g(x)):

Before:         y = (8-3x)/2

After:            x=(8-3y)/2

                      (solve)

                   2x= 8-3y (Multiplying both sides by 2)

                   2x-8 = -3y (Subtracting 8 both sides)

                   (2x-8)/-3 =y (Dividing by -3 both sides)

                   (8-2x)/3 = y  (Multiplying the negative in numerator[Not necessary, but preferred by most!])

Hope this helps!